1997
DOI: 10.1007/s004380050391
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum-sensitive mutants of Saccharomyces cerevisiae

Abstract: We are developing budding yeast, Saccharomyces cerevisiae, as a genetic system for the study of tolerance to the trivalent aluminum cation (Al3+). We have isolated eight mutants that are more sensitive to Al3+ than the wild type. Each mutant represented a different complementation group. A number of the mutants were pleiotropic, and showed defects in other stress responses, changes in tolerance to other metal cations, or abnormal morphology. Two mutants also showed increased dependence on supplemental Mg2+ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 40 publications
1
33
0
1
Order By: Relevance
“…SLK1 belongs to the same pathway of SLT2 MAP kinase (SLT2 pathway) and encodes the corresponding MAP kinase-kinase. Schott and Gardner (1997) have shown that yeasts with a mutant SLT2 pathway are aluminum sensitive, these authors suggesting that this results in failure of the cells properly to cease division in the presence of toxic levels of aluminum. The expression of NtGDI1 in response to aluminum toxicity seems to cause an increased afflux of aluminum (Ezaki et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…SLK1 belongs to the same pathway of SLT2 MAP kinase (SLT2 pathway) and encodes the corresponding MAP kinase-kinase. Schott and Gardner (1997) have shown that yeasts with a mutant SLT2 pathway are aluminum sensitive, these authors suggesting that this results in failure of the cells properly to cease division in the presence of toxic levels of aluminum. The expression of NtGDI1 in response to aluminum toxicity seems to cause an increased afflux of aluminum (Ezaki et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A long evolutionary history of exposure to Al is likely to favor the development of highly adapted genotypes with polygenic control of resistance, because Al resistance can be modified by a considerable number of genes (Larsen et al, 1996;Schott and Gardner, 1997;Ezaki et al, 1999Ezaki et al, , 2000. Species of agricultural interest tend to be less Al-resistant than "wild species" (Wheeler et al, 1992;Crawford and Wilkens, 1998).…”
Section: Al Resistance Of Signalgrass Is Outstandingly High Compared mentioning
confidence: 99%
“…Although yeast apoptosis is still controversial (LeBrasseur, 2004), abundant evidence suggests that yeast is an excellent model system because it has been extensively characterized both biologically and genetically (Fleury et al, 2002b;Jin and Reed, 2002;Madeo et al, 2004). Moreover, yeast has several advantages for research on Al toxicity and tolerance (MacDiarmid and Cardner, 1996), and parallels between yeast and plant systems are evident on some mechanisms of Al toxicity (Schott and Gardner, 1997;MacDiarmid and Gardner, 1998;Ezaki et al, 1999;Anoop et al, 2003). Therefore, clarifying how Al induces yeast cells to undergo PCD would be helpful to better understand the complex mechanisms of Alinduced PCD in plants.…”
mentioning
confidence: 99%